Mesoscale eddies and the impact of coastal iron supply on primary production in the South Pacific Subtropical Front. (October 2022) - Chiswell, Stephen M.; Boyd, Philip W.; Sander, Sylvia G.; Ellwood, Michael J.; Milne, Angela
Abstract: Subtropical and subantarctic waters either side of the southern hemisphere Subtropical Front are considered iron-limited, suggesting production within the front is dependent on a supply of iron from atmospheric deposition, zonal advection of coastal water, or upwelling. We present the results from a one-day biogeochemical survey in Subtropical Water east of the North Island, New Zealand, in a region where mesoscale cyclonic and anticyclonic eddies entrain chlorophyll in filaments around the eddies. There was no significant relationship between upper mixed layer chlorophyll and any physical or macronutrient quantity. However, chlorophyll was significantly positively correlated with dissolved iron. A simple model suggests that while vertical entrainment of iron into the upper mixed layer occurred, most of the dissolved iron in the eddy was due to entrainment of high-iron coastal water into low-iron offshore Subtropical Water, and that this iron supports primary production in otherwise iron-deficient water. We suggest that a significant component of the total primary production within the Subtropical Front may be determined by mesoscale eddy induced lateral advection of iron. Highlights: Dissolved iron limits primary production in offshore South Pacific surface waters. Phytoplankton is elevated in high-iron filaments in mesoscale eddies east of New Zealand. Iron in these eddies is due to entrainment of high-iron coastal water into offshore water. The resultant eddy-driven flux of iron supports production in the Subtropical Front.